Whether ambulatory electroencephalogram and visual tracking system could be the new strategy for pain assessment? - Ma, Xiaqing; Zhang, Hong; Xu, Tao (Frontiers in Neuroscience, 2023)
The human pain experience is a complex multi-faceted symptom. Effective pain management begins with a comprehensive assessment. However, a plethora of existing assessment tools for pain assessment focus more on self-report of pain intensity but lack of multi-dimensional impersonal assessment. These unidimensional scales, which capture self-reported levels of pain intensity, not only underestimate the complexity of the pain experience, but also lack stability and objectivity in their own assessments of pain intensity. Therefore, we propose a hypothesis that using scientific and technological means, such as visual tracking and surveillance system, ambulatory electroencephalogram and other techniques, combined with psychological assessment pictures and existing scales, to comprehensively evaluate pain may provide a new method for more effective clinical treatment of pain, especially chronic severe pain.